Investigation the application of niosome as a nanocarrier for sage (Salvia officinalis L.) extract by spectroscopy and chemometrics - Somayeh Samaei, Seyedeh (2021)
Objetive: Investigation the application of niosome as a nanocarrier for sage (Salvia officinalis L.) extract by spectroscopy and chemometrics. Material and Method: In this study,niosome nanoparticles containing cholesterol and without cholesterol were prepared by thin film hydration method. Ethanol extract of sage was extracted by microwave and loaded inside the niosome nanoparticles. The size of the nanoparticles was determined by field imaging scanning electron microscopy (FE-SEM). The zeta potential of the niosomes was determined by Dynamic light scattering (DLS). to investigate the type of interactions between surfactants and cholesterol used in the niosome structure, Fourier transform infrared spectroscopy (FT-IR) was used. Drug release was investigated for 5 consecutive days in phosphate buffer salin (PBS) 0/01 M with pH=7.4 at T=370C. Results:The zeta potential of the niosomes with cholesterol and without cholesterol was -24/1&-15/6 mv . The loading capacity of the drug in the concentration range (1-3% w / w of niosum) for both types of niosome was between 61% and 93%. Conclusion: This results show that the release rate of niosme with cholesterol is significantly more regular and lower than of niosome without cholesterol. In general, it can be concluded that niosome can be a suitable nano-carrier for delivery of hydrophilic extract of the sage.